2012
DOI: 10.2147/ijn.s32579
|View full text |Cite
|
Sign up to set email alerts
|

Simple filter microchip for rapid separation of plasma and viruses from whole blood

Abstract: Sample preparation is a significant challenge for detection and sensing technologies, since the presence of blood cells can interfere with the accuracy and reliability of virus detection at the nanoscale for point-of-care testing. To the best of our knowledge, there is not an existing on-chip virus isolation technology that does not use complex fluidic pumps. Here, we presented a lab-on-a-chip filter device to isolate plasma and viruses from unprocessed whole blood based on size exclusion without using a micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…The device used an external vacuum pump to provide negative pressure for plasma extraction. Wang et al 30 reported on a similar microfluidic-based plasma separation chip with an embedded 2-μm pore size membrane filter for plasma and HIV virus separation. To avoid the use of a pump, Wang et al 30 extracted plasma containing HIV virus from 40 μL of whole blood by washing it with 300 μLPBS buffer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The device used an external vacuum pump to provide negative pressure for plasma extraction. Wang et al 30 reported on a similar microfluidic-based plasma separation chip with an embedded 2-μm pore size membrane filter for plasma and HIV virus separation. To avoid the use of a pump, Wang et al 30 extracted plasma containing HIV virus from 40 μL of whole blood by washing it with 300 μLPBS buffer.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 30 reported on a similar microfluidic-based plasma separation chip with an embedded 2-μm pore size membrane filter for plasma and HIV virus separation. To avoid the use of a pump, Wang et al 30 extracted plasma containing HIV virus from 40 μL of whole blood by washing it with 300 μLPBS buffer. Such extensive dilution may, however, adversely affect the limit-of-detection, which is critical in viral load detection.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [36] developed a microfluidic-based plasma separation device with a 2-μm pore size membrane filter, which separated plasma and HIV virus from pre-diluted whole blood with virus recovery efficiencies ranging from 73.1% to 82.5%. However, the pre-dilution of blood reduces the ultimate limit of detection, which is critical in HIV viral load quantification.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Advances in nanotechnology and microfluidic platforms rapidly enable significant developments of biosensing technologies and medical diagnostics (Wang et al, 2012a; Wang et al, 2012b). Particularly, advances in micro-nanofabrication technologies allow for developing rapid, user-friendly, accurate and specific diagnostic tools/methods, which achieve low detection limits of the target analytes/cells.…”
Section: Recent Advances In Nanotechnological Tools For Diagnosis mentioning
confidence: 99%
“…Another SPR-based HBV detection technology was reported to detect recombinant HBV surface antigens (HBsAg) by immobilizing anti-HBsAg polyclonal antibodies to a dextran layer of N-hydroxysuccinimide activated CM5 sensor chips (Hwang et al, 2005). HBsAg is reported as the most important biomarker for diagnosis HBV, and its serum levels exhibit an acute and chronic HBV infection and probable infectivity (El-Ghitany and Farghaly, 2013; Wang et al, 2010b). This microfluidic-integrated SPR platform is focused to examine the binding characteristics between recombinant HBsAg and polyclonal antibody, and this binding analysis demonstrated that approximately six antibody molecules captured one HBsAg molecule at saturation level.…”
Section: Recent Advances In Nanotechnological Tools For Diagnosis mentioning
confidence: 99%